Intrathyroidal thyroglossal duct cyst presenting as chronic thyroiditis: Case report and narrative review of the literature - Arsheed Hussain Hakeem; Hassaan Javaid; Hima Bindu Rallabandi; Fozia Jeelani Wani (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2020)
The presence of the thyroglossal duct cyst (TDC) within the thyroid gland is of rare occurrence as only 16 cases have been documented to date. It is even rare for the intrathyroidal TDC to present as infective thyroiditis as only one case has been reported in the scientific literature. We report a case of intrathyroidal TDC which presented as recurrent episodes of thyroiditis in a 13-year-old female. Diagnostic work-up, management, and review of pertinent scientific literature is also presented. To the best of our knowledge, this is the second case of intrathyroidal TDC which has presented as chronic recurrent thyroiditis. It is the first case of the intrathyroidal TDC with chronic thyroiditis reported in the pediatric age group.